Exploring the Tradition of 'Pamantang': Prohibitions and Beliefs Surrounding Pre-Marriage Practices in the Banjar Society - Fithriani, Ahda; Rahim, Niska Kamalia (PT. Sharia Journal and Education Center, 2024)
Abstract In the Banjar society, prohibitions or restrictions are referred to as